Pengaruh Lingkungan Sekolah Islam Terhadap Pengembangan Jiwa Wirausaha Siswa di Lampung - Hery Syaputra; M.Fajarrudin; Fajri Husaini; Maisuhetni; Moh Fakhrurozi (Universitas Muhammadiyah Metro, 2026)
This research aims to analyze the influence of the Islamic school environment on the development of an entrepreneurial spirit among students in Lampung. A school environment that is conducive and supports entrepreneurial activities can help foster entrepreneurial interest and skills in students from an early age. This research uses a literature review method by analyzing 15 relevant scientific articles, published between 2015-2023. The research results show that the Islamic school environment has a positive influence on the development of students' entrepreneurial spirit through the integration of Islamic values with entrepreneurial principles, a supportive curriculum, practical programs, and character development. Contributing factors include the integration of Islamic values, entrepreneurship curriculum, internship programs, entrepreneurial character development, use of learning technology, and support from alumni networks. This research concludes that Islamic schools in Lampung play an important role in forming a generation of young entrepreneurs who are ethical and innovative. Further empirical research is needed to measure the long-term impact of entrepreneurship education in Islamic schools on the career and entrepreneurial success of alumni.